ANALYZE THE GROWTH RATE OF A PREY-PREDATOR SYSTEM WITH SIMULATION USING MATLAB - Mehenaz Aktar Mimi, Md. Eaqub Ali, Kanak Chandra Roy, Shuvo sarker, Rezaul Karim, Pinakee Dey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Mathematical models and common sense suggest that a connected system of predator and prey should cycle: predation decreases prey populations to low rates, predator numbers rise, and prey populations rise continually. One such model that models predator-prey interactions is the Lotka-Volterra Model. According to our findings, both prey and predator growth are reliant on additional food sources as well as one another. Utilizing this technique, the stability of the linearized equilibrium point is analyzed. The findings indicate that the equilibrium point in the positive quadrant is stable. To demonstrate the behavior of the cohabitation of prey and predator populations, certain instances are offered. Additionally, it illustrates how the prey or predator population behaves while they are absent, what interactions occurred between them, and evaluates the numerical simulation for various parameters. The biological ramifications of our findings are further touched upon in the study's conclusion.